Muscle health in ankylosing spondylitis: effects of disease duration, inflammation, education level, and spinal mobility on skeletal muscle atrophy - Jiawen Hu; Yiwen Wang; Zhimeng Yu; Yinan Zhang; Xiaojian Ji; Lulu Zeng; Jiaxin Zhang; Shiwei Yang; Kunpeng Li; Jian Zhu; Jianglin Zhang; Yinghua Liu; et al. (Therapeutic Advances in Musculoskeletal Disease)
Background: Ankylosing spondylitis (AS) is a progressive chronic disease that primarily affects the axial skeleton, leading to significant musculoskeletal impairment. This condition may extend its inflammatory impact to peripheral muscles, potentially resulting in muscle wasting. Objectives: The study aimed to investigate the prevalence of sarcopenia among AS patients, to determine the specific cutoff values for muscle status, and to identify risk factors that may impact muscle status in AS patients. Design: A cross-sectional study was conducted involving consecutive AS patients attending the Department of Rheumatology and Immunology at the First Medical Center of the Chinese PLA General Hospital. Clinical characteristics and body composition were evaluated. Methods: Based on the Asian Working Group for Sarcopenia criteria, the prevalence of sarcopenia among AS patients were calculated. Additionally, specific cutoff values for muscle mass and muscle strength in AS patients were analyzed. Univariable and multivariable logistic regression analyses were employed to scrutinize risk factors impacting muscle status in AS patients, including appendicular skeletal muscle mass index (ASMI) and grip strength. Results: Measurements of body composition, including ASM at 22.79 kg and ASMI at 7.69 kg/m², were significantly lower compared to the healthy control group ( p  < 0.05). The prevalence of sarcopenia, as identified by the sex-specific fifth percentile, is 8.66% in AS patients. In our study, the ASMI cutoffs were set at 7.48 kg/m² for males and 5.63 kg/m² for females. Logistic regression analysis revealed that AS patients who had a longer disease duration, lower level of education, elevated inflammatory markers, and a higher Bath Ankylosing Spondylitis Metrology Index (BASMI) were more likely to experience a decrease in ASMI. Regarding the muscle strength, lower education level and higher Bath Ankylosing Spondylitis Functional Index were correlated with a reduced grip strength in individuals with AS. Conclusion: Our study indicates that AS patients may have a diminished muscle status. Although the incidence of sarcopenia among AS patients is relatively low, a notable subset does suffer from muscle atrophy. Variables such as disease duration, education level, inflammatory markers, and BASMI are likely to influence muscle status in AS patients, warranting consideration in clinical management and intervention strategies.